The effect of chrysin‐loaded nanofiber on wound healing process in male rat. (17th October 2017) - Mohammadi, Zoheyr; Sharif Zak, Mohsen; Majdi, Hasan; Seidi, Khaled; Barati, Meisam; Akbarzadeh, Abolfazl; Latifi, Ali Mohammad
Abstract : Wound healing is an inflammatory process. Chrysin, a natural flavonoid found in honey, has been recently investigated to have anti‐inflammatory and antioxidant effects. In this work, the effects of chrysin‐loaded nanofiber on the expressions of genes that are related to wound healing process such as P53, TIMPs, MMPs, iNOS, and IL‐6 in an animal model study were evaluated. The electrospinning method was used for preparation the different concentrations of chrysin‐loaded PCL‐PEG nanofiber (5%, 10%, and 20% [w/w]) and characterized by FTIR and SEM. The wound healing effects of chrysin‐loaded PCL‐PEG nanofiber were in vivo investigated in rats, and the expressions of genes related to wound healing process were evaluated by real‐time PCR. The study results showed chrysin‐loaded PLC‐PEG compared to chrysin ointment and control groups significantly increase IL‐6, MMP‐2, MMP‐8, MMP‐9, TIMP‐1, and TIMP‐2 ( p  < .05). On the other hand, nanofibers containing chrysin significantly decreased p53 and iNOS expression compared to chrysin ointment and control groups ( p  < .05). According to the results, chrysin‐loaded PCL‐PEG‐PCL nanofibers have positive effects on the expression of the genes that have pivotal role in wound healing. Abstract : The average diameter of PCL‐PEG nanofibers and chrysin‐loaded PCL‐PEG nanofibers were about the range of 50–150 nm. It was observed from these micrographs that the nanoparticles of PCL‐PEG exhibited smooth surfaces and uniform structures with beads. Morphology of PCL‐PEG nanofibres: (i) free of chrysin; (ii) 5% (w/w) chrysin‐loaded PCL‐PEG nanofiber; (iii) 10% (w/w) chrysin‐loaded PCL‐PEG nanofiber; (iv) 15% (w/w) chrysin‐loaded PCL‐PEG nanofiber.